Investigation of the Effect of Tarantula cubensis Extract on Acute Phase Response - Corum, Orhan; Er, Ayse; Dik, Burak (Acta Scientiae Veterinariae, 2016)
Background: Tarantula cubensis alcoholic extract is used to accelerate wound healing and to relieve edema in many animal species. In addition, it may be useful for many infectious diseases. Considering to these effects, it is believe that these effects may be on immune system. Cytokines (tumor necrosis factor alpha, interleukin-1 beta, interleukin-6, interleukin-10 and interferon gamma) secreted by immune cells and acute phase proteins (haptoglobin, alpha 1 acid glycoprotein, serum amyloid A) secreted by liver play role in acute phase response. The aim of the present study was to determine the effect of Tarantula cubensis alcoholic extract on cytokine and acute phase protein levels in sheep. Materials, Methods & Results: Tarantula cubensis alcoholic extract (6 mL/sheep, subcutaneously, single dose) was administered to 6 healthy sheep. Blood samples were obtained before (0 h) and after treatments at 2, 4, 8, 12, 24 and 48 h. Then, blood samples were centrifuged to obtain serum samples. Acute phase cytokines such as serum tumor necrosis factor alpha, interleukin-1 beta, interleukin-6, interleukin-10, interferon gamma and acute phase proteins such as haptoglobin, alpha 1 acid glycoprotein and serum amyloid-A concentrations were determined with commercially available kits on ELISA reader. Administration of Tarantula cubensis alcoholic extract caused fluctuations in tumor necrosis factor alpha, interleukin-1 beta, interleukin-6, interleukin-10, interferon gamma levels in sheep. In addition, levels of haptoglobin, alpha 1 acid glycoprotein, serum amyloid A showed fluctuations. But, these fluctuations in acute phase cytokines and acute phase proteins were not statistically significant (P > 0.05). Discussion: Tarantula cubensis alcoholic extract, homeopathic medicine, is used trauma, retentio secundinarium, tendinitis, bluetongue, foot and mouth, metritis and arthritis in many animal species including sheep. Cytokines, secreted against various stimulus including infectious diseases, play role in wound healing and in the regulation of the immune system. In current study, administration of Tarantula cubensis alcoholic extract lead to fluctuations in tumor necrosis factor alpha, interleukin-1 beta, interleukin-6, interleukin-10 and interferon gamma levels, but these changes were not statistically significant (P > 0.05). Non-statistical fluctuations in cytokines result from inadequate immunological response of sheep against to Tarantula cubensis alcoholic extract. Also, use of molecular analysis techniques may be changed these results. Acute phase proteins are significantly secreted from the liver during the acute phase response. In current study, administration of Tarantula cubensis alcoholic extract in sheep caused non-statistifical fluctuations on haptoglobin, alpha 1 acid glycoprotein and serum amyloid A levels (P > 0.05). Tumor necrosis factor alpha and interleukin-1 beta stimulate synthesis of interleukin-6. Interleukin-6 provides synthesis of acute phase proteins in liver. Non-statistical fluctuations in acute phase proteins result from inadequate stimulus of IL-6. In conclusion, it may be stated that administration of Tarantula cubensis alcoholic extract has no distinctive effect on the acute phase response. However, when Tarantula cubensis alcoholic extract is administered repeated times or other acute phase parameters are evaluated, different results may be observed.